Household agrobiodiversity management on Amazonian Dark Earths, Oxisols, and floodplain soils on the Lower Madeira River, Brazil - Kawa, Nicholas C.; Clavijo-Michelangeli, José A.; Clement, Charles Roland (Human Ecology, 2015)
Smallholder farmers play a critical role in the maintenance of global agrobiodiversity. However, the social and environmental factors that shape agrobiodiversity and its management in rural smallholder communities are still debated among scholars. This study examines variation in the diversity of useful plant species (i.e.; species richness) managed by households located in three distinct environments along the Lower Madeira River in the Central Brazilian Amazon: Amazonian Dark Earths (ADE), upland Oxisols (OX), and floodplain soils (FP). Among the 106 households studied, those located on ADE managed a significantly higher number of useful species than those on floodplain soils but not than those on Oxisols. A generalized linear mixed effects model indicates that the age of the household head, number of household members and adults, and area of land under cultivation are statistically significant factors that influence species richness across all households. Ethnographic data are employed to contextualize these findings and discuss other influences on agrobiodiversity management in rural Amazonian communities, including regional historical ecology and the life histories of individual farmers. © 2015 Springer Science+Business Media New York.